ANALISIS PERAMALAN PENJUALAN SEMEN MENGGUNAKAN METODE SINGLE MOVING AVERAGE DAN SINGLE EKSPONENTIAL SMOOTHING - Afandi, RIzqi Ramadhani (JUSTI (Jurnal Sistem dan Teknik Industri), 2025)
UKM Bahan Bangunan Ismail Ali is a company engaged in the sale of building materials, with one of its products being Portland cement under the brand name "SEMEN GRESIK." Sales tend to be fluctuating, making it difficult to predict. The SME faces capital limitations, so the expectation is for the finances to continue circulating and to gain opportunities for greater profits without disrupting the stock. This study will forecast using the Single Moving Average and Single Exponential Smoothing methods.The forecast results for SEMEN GRESIK for the next period are as follows. Single Moving Average with a length of 2 is 216. Single Moving Average with a length 3 is 216.Single Moving Average with a length of 4 is 213.75. Single Exponential Smoothing with α 0.0645194 is 216.148. Both methods showed a very good MAPE (Mean Absolute Percentage Error) value. The verification of the Single Moving Average method with a length of 2 showed conditions outside of control, while the Single Moving Averages with lengths 3 and 4 and the Single Exponential Smoothing method did not have conditions outside of control and represented the data pattern well. The Single Exponential Smoothing method is recommended because, based on the error comparison, this method is more accurate and has been verified to represent the data pattern better than the Single Moving Average method. Keywords : Forecasting, Single Moving Average, Single Eksponential Smoothing